2017
DOI: 10.1002/2017gl072549
|View full text |Cite
|
Sign up to set email alerts
|

Is there a stratospheric pacemaker controlling the daily cycle of tropical rainfall?

Abstract: Rainfall in the tropics exhibits a large, 12 h Sun‐synchronous variation with coherent phase around the globe. A long‐standing, but unproved, hypothesis for this phenomenon is excitation by the prominent 12 h atmospheric tide, which itself is significantly forced remotely by solar heating of the stratospheric ozone layer. We investigated the relative roles of large‐scale tidal forcing and more local effects in accounting for the 12 h variation of tropical rainfall. A model of the atmosphere run with the diurna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In fact, significant coherence between precipitation and zonal wind extends to the 50-hPa level but again not for meridional wind (not shown). Some previous works suggest that even fast dynamical waves like atmospheric tides can modulate precipitation (e.g., Yasunaga et al 2013;Kohyama and Wallace 2016;Sakazaki et al 2017). However, this apparent modulation of precipitation by vertical motions in a deep dry Kelvin wave in Figs.…”
Section: Fig 4 As Inmentioning
confidence: 80%
“…In fact, significant coherence between precipitation and zonal wind extends to the 50-hPa level but again not for meridional wind (not shown). Some previous works suggest that even fast dynamical waves like atmospheric tides can modulate precipitation (e.g., Yasunaga et al 2013;Kohyama and Wallace 2016;Sakazaki et al 2017). However, this apparent modulation of precipitation by vertical motions in a deep dry Kelvin wave in Figs.…”
Section: Fig 4 As Inmentioning
confidence: 80%
“…For example, the daily precipitation patterns that are characteristic in many regions of the tropics remain poorly understood (Kikuchi and Wang 2008;Sakazaki et al 2017). Recognition of biological processes may help (Makarieva and Gorshkov 2007;Sheil and Murdiyarso 2009;Sakazaki et al 2017;). We know that transpiration often ceases temporarily, or periodically, after high rates have been achieved (Zhang et al 2013).…”
Section: New Insightsmentioning
confidence: 99%
“…Previous studies evaluating the representation of solar tides in the stratosphere and the lower mesosphere in re-analyses have mainly considered only S 1 (24 h) tides. An early study by Swinbank et al (1999) investigated the S 1 migrating tide in the stratosphere as represented in the Goddard Earth Observing System (GEOS) version 2 analysis data (one of the predecessors of MERRA and MERRA-2 reanalyses). They found that the GEOS-2 tidal amplitude in the free-running model is reduced by assimilating satellite data, particularly data from the stratospheric sounding unit (SSU).…”
Section: Introductionmentioning
confidence: 99%